Overturned Rhythmic Banding in the Huntly Gabbro of Aberdeenshire - Shackleton, R. M. (Geological Magazine, 1948)
In a recent letter to this journal, Stewart and Wager (1947) record the occurrence of rhythmic banding in the Cuillin gabbro of Skye. Apparently, before this the only described British example of rhythmic, banding was in the Belhelvie Complex of Aberdeenshire (Stewart, 1946). In view of the interest in these structures aroused by Wager and Deer's vivid and illuminating account of the Skaergaard Complex of East Greenland (Wager and Deer, 1939), a preliminary note on a more accessible occurrence where rhythmic banding is very beautifully displayed, in excellent quarry sections, seems desirable. This occurrence is in the Huntly complex of Aberdeenshire.